Design of In Vitro Bioactive Hybrid Materials from the First Generation of Amine Dendrimers as Nanobuilding Blocks. Issue 15 (21st February 2013) - González, Blanca; Colilla, Montserrat; Vallet‐Regí, María
Abstract In this work, the first generation of poly(propyleneimine) dendrimers were functionalized with alkoxysilane terminal groups and subjected to one of two different sol–gel process that followed two different catalytic pathways, that is base‐ or acid‐catalyzed pathways. Thus, two series of new organic–inorganic hybrid materials were obtained in the form of monolithic pieces with differences in terms of both morphology and silanol content, which originated from the different sol–gel pathway that was followed. Moreover, calcium ions were added into the hybrid composition to promote in vitro bioactivity and phosphorous sources were used during the sol–gel step to obtain an earlier bioactive response. Characterization of these organic–inorganic hybrid materials was performed by means of thermogravimetric and elemental analyses, Fourier transform infrared spectroscopy (FTIR), solid state 13C, 29Si and 31P magic‐angle spinning (MAS) nuclear magnetic resonance (NMR) spectroscopy, N2‐adsorption isotherms, mercury‐intrusion porosimetry, and ζ‐potential measurements. The in vitro bioactivity of the dendritic hybrid networks was evaluated by soaking the materials in simulated body fluid and the results were explained in terms of the composition of the hybrids and the sol–gel route that was followed to prepare them.